Gender, age and grade level differences in psychological factors among immigrant francophone adolescent learners in the South African school setting - Kananga Robert Mukuna (International Journal of Studies in Psychology)
Psychological factors are important for boys or girls, depending on age and grade level. This study examines emotional regulation, aggressiveness, empathy, and sympathy, as psychological factors to peer interaction, manifest in adolescence. Eighty-three participants were conveniently and purposively selected at South African schools (N= 83, 52 girls and 31 boys, aged between 14 and 19 years). A psychological factors scale was purposively employed as a data collection instrument. The chi-square results partially confirmed previous results, namely, aggressiveness and sympathy, by gender and age. However, this did not apply to emotional regulation. This study recommended that the South African education system consider aggressiveness a psychological factor, playing a critical role in violence at schools among young adolescents.